2000
DOI: 10.1046/j.1365-2648.2000.01454.x
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial infarction: survivors’ and spouses’ stress, coping, and support

Abstract: Despite evidence that spouses play an important role in the recovery of MI survivors, there have been few studies of pertinent psychosocial factors from the perspectives of both survivors and spouses. Accordingly, the aim of this study was to describe stress, coping strategies and social support experienced by survivors and spouses. This study was limited to first-time MI to focus on a time of uncertainty and transition. Twenty-eight persons (14 couples) participated. Both survivors and their spouses reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
129
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(138 citation statements)
references
References 60 publications
8
129
1
Order By: Relevance
“…This research also suggests that nurses do not routinely inquire about patients sexuality and provide little teaching and guidelines for individuals resuming sexual activity following a cardiac event [13,[17][18][19][20][21][22]. When patients' views were sought, they reported that they would like service providers to take their full sexual history and that they would be comfortable with these discussions [23].…”
Section: Introductionmentioning
confidence: 99%
“…This research also suggests that nurses do not routinely inquire about patients sexuality and provide little teaching and guidelines for individuals resuming sexual activity following a cardiac event [13,[17][18][19][20][21][22]. When patients' views were sought, they reported that they would like service providers to take their full sexual history and that they would be comfortable with these discussions [23].…”
Section: Introductionmentioning
confidence: 99%
“…When MI patients engage in the physical exertion associated with sexual activity, they fear precipitating a new MI and thereby cardiac death 8 . A study by Stewart et al 9 revealed that inadequate and differing information about sexual intercourse from healthcare professionals generated anxiety and fear in MI patients. Women who had had an MI reported a lack of information and counselling about sexual issues from healthcare professionals [10][11][12] , although Steinke and Patterson-Midgley 13 did not find any differences between men and women in relation to the provision of sexual counselling.…”
Section: Introductionmentioning
confidence: 99%
“…Research indicates that patients and spouses share similar experience of stressors [3]. When partners suffer more anxiety than the patient, it worsens the patient's psychosocial adjustment and outcome [4].…”
Section: Introductionmentioning
confidence: 99%